Mother-Child Interaction on Independence of Children with Intellectual Disabilities - Kurnia, Fitra Nanda; Eva Riany, Yulina; Puspitawati, Herien; Herawati, Tin (Universitas Islam Indonesia, 2025)
Developmental tasks are a series of responsibilities that arise at each stage of life. Inchildren with intellectual disabilities, the development of independence has been observed toface more complex challenges due to certain limitations. To effectively support theindependence of this demographic, the role of the family in protecting respective rights has beenidentified to be an important aspect. Therefore, this study aims to analyze the correlation andeffect of mother-child interaction (MCI) on independence of children (IC) with intellectualdisabilities in Bogor City. The subjects consisted of 155 mothers who had children withintellectual disabilities aged 2-18 years. In order to achieve the stated objective, data werecollected using a non-probability sampling method with a purposive sampling method. Theinstruments used include the Parent-Child Relationship Schema Scale (PCRSS) developed byDixon et al. (2014) and Children Helping Out: Responsibilities, Expectations, and Support(CHORES) model introduced by Dun (2004). The results showed the presence of a positivecorrelation between MCI and IC (path coefficient (β) = .362, p = .000). Furthermore, severaldimensions of MCI, such as attention, mutual assistance, and affection, were significantly relatedto the independence of the observed demographic. Based on these results, it was inferred that ahealthy MCI led to the instillation of a higher level of independence in children with intellectualdisabilities. The effect test results showed a significant positive effect between MCI and IC, witha path coefficient of .371, a t-value of 4.016, and a very low p-value (p < .000). This reflected thatMCI had a significant impact on IC level.